Effects Of Auditors’ Culpability On Creative Accounting In Southwest Nigeria - Ojuolape , Tunde Charles; Akinnola , Tony Mofehintolu (Archives of Business Research, 2020)
The study examined the effects of auditors’ culpability on creative accounting in Southwest Nigeria. The study employed questionnaire to gather data from 66 managers and 66 accountants. The study was analysed with the use of descriptive statistics and One Way Analysis of Variance to test the hypotheses of the study. The study found that auditors’ culpability has no effect on creative accounting in private sector in Nigeria. The study revealed that that the reasons for statutory auditors engaging in creative accounting practices have effect on the practice of creative accounting in Nigeria. The study recommends that accountants should uphold high ethical standards and maintain integrity in all their professional dealings. Accountants should not allow personal prejudice or bias to override the principle of objectivity, transparency and due diligence in the profession. Auditors must not only develop questioning mind, skill for critical assessment of audit evidence but must also exercise these skills with reasonable care and diligence.